COCHLEAR IMPLANTATION IN IRAN - M.H. Khalessi; S. Abdi; M.T. Khorsandi (Acta Medica Iranica, 1996)
Deafness has been considered a non - resolving problem until the invention of cochlear implantation (CI). We are reporting the pre- and post-operative results of 14 patients underwent CI, for the first time in Iran, at the cochlear implantation Clinic of Tehran University of Medical Sciences. Four of our patients were able to hold a telephone conversation without difficulty 3 months post-operatively and the rest achieved considerable scores on audiologic tests and a remarkable improvement over 9 month interval between the two sets of tests. Also we have addressed the dramatic improvement in the quality of life of these patients in this paper as well as the results of promontory stimulation and audiometry.